Bluestar's prophecy - Hunter, Erin. (New York : Harper, 2009)
Bluefur, a warrior of ThunderClan, struggles under the weight of a prophecy that promises her glory as Clan leader, but also spells out her ultimate demise.
"Warriors Super Edition."
Keywords: Cats -- Fiction; Prophecies -- Fiction; Adventure and adventurers -- Fiction; Fantasy